Introduction to Neogeography - Turner, Andrew (O'Reilly short cuts., 2006)
Neogeography combines the complex techniques of cartography and GIS and places them within reach of users and developers. This Short Cut introduces you to the growing number of tools, frameworks, and resources available that make it easy to create maps and share the locations of your interests and history. Learn what existing and emerging standards such as GeoRSS, KML, and Microformats mean; how to add dynamic maps and locations to your web site; how to pinpoint the locations of your online visitors; how to create genealogical maps and Google Earth animations of your family's ancestry.